Developing key competences in the light of learning theory - the perspective of the teacher and student - Barbara Skałbania (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
The content of the article concerns the currently important issue, which is key competences in school education of students. Shaping them is an important task and at the same time a challenge for a modern school, but it raises a number of organizational and methodological doubts among teachers. The purpose of theoretical considerations is to analyze the issue in relation to contemporary learning theories and the issue of competences seen from the perspective of the student's and teacher's development needs. The analyzes are accompanied by a reflection on the practice of early childhood education focused on the holistic development of the child.